Optimal Investment Strategy Selection: Real Options Approach in Indonesia’s Oilfield Drilling Services - Muhammad Reihant Muzadi; Oktofa Yudha Sudrajad (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study develops an analytical framework to select the optimal investment strategy for an Indonesian state-owned oilfield services company, addressing CAPEX gaps and comparing static and dynamic valuation approaches under uncertainty. The study employs a case-based quantitative valuation design. Discounted Cash Flow (DCF) is used as the A case-based quantitative design uses Discounted Cash Flow (DCF) to assess project feasibility in varying demand scenarios, while Real Options Valuation (ROV), supported by Monte Carlo simulation, evaluates the value of managerial flexibility. DCF shows the project is unfeasible in low demand but viable in base and high scenarios. ROV, incorporating flexibility, provides higher investment values, turning a negative NPV in the low-demand case into a positive Total Investment Value (TIV), indicating strategic viability under uncertainty. Integrating Real Options Valuation into the firm’s capital budgeting process improves investment decision making compared with relying on Discounted Cash Flow alone. The analysis focuses on a single Indonesian state-owned oilfield services company, with uncertainty primarily in market demand and volatility, limiting generalizability to other firms or environments. This study provides a decision-making framework for investment strategy selection in oilfield services by comparing DCF and ROV, showing how option value influences decisions under uncertainty through simulation-based valuation.